2006
DOI: 10.1080/00365540500440353
|View full text |Cite
|
Sign up to set email alerts
|

‘Break-point Checkerboard Plate’ for screening of appropriate antibiotic combinations against multidrug-resistant Pseudomonas aeruginosa

Abstract: Increase of multiple drug resistant Pseudomonas aeruginosa (MDRP) is becoming a serious problem in the clinical setting. Although the checkerboard method to determine FIC index and synergistic effects of antibiotic combinations is useful, it is not well adapted to a routine test, mainly because of its time-consuming and labor-intensive nature. Here we report 'Break-point Checkerboard Plate', in which breakpoint concentrations, such as 'S' (sensitive) and 'I' (intermediate), were combined in a microtiter plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 28 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Tateda et al reported using a breakpoint checkerboard plate method on 12 P. aeruginosa isolates tested with imipenem and polymyxin B, with all 12 isolates showing synergy (12). Three studies (13)(14)(15) reported using the area under the bacterial killing curve (AUBKC) against P. aeruginosa, K. pneumoniae, or A. baumannii.…”
Section: Resultsmentioning
confidence: 99%
“…Tateda et al reported using a breakpoint checkerboard plate method on 12 P. aeruginosa isolates tested with imipenem and polymyxin B, with all 12 isolates showing synergy (12). Three studies (13)(14)(15) reported using the area under the bacterial killing curve (AUBKC) against P. aeruginosa, K. pneumoniae, or A. baumannii.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, numerous plates are required when investigating various drugs simultaneously. In contrast, the "Break-point Checkerboard Plate," which was designed by Tateda et al in 2006, incorporates only two concentrations of eight antimicrobials near the breakpoints. By employing this novel method, we could evaluate three or four consecutive concentrations close to the CLSI breakpoints for each drug.…”
Section: Discussionmentioning
confidence: 99%
“…Among several methods of investigating in vitro efficacy of drugs in combination, the checkerboard method is most widely used because of its low cost and labor requirements (Odds, 2003). Further, the "Break-point Checkerboard Plate" allows for the simultaneous evaluation of 19 different combinations of drugs at clinically relevant concentrations on a single 96well microplate (Tateda et al, 2006). Recently, this technique has proven useful in daily clinical practice as a screening method for drug combinations exhibiting in vitro combined efficacy on multi-drug resistant Pseudomonas (MDRP) in Japan (Nishio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, appropriate antibiotic treatment using prolonged bacterial surveillance culture should be considered, particularly in ATL patients with persistent compromised cellular immunity. Moreover, because of a limitation of treatment active on multi-drug resistant gram negative rods, particularly Pseudomonas aeruginosa, at the present situation, the introduction of new treatment options, including antibiotic combination therapy using a "break-point checker board plate" and developing antibiotic agents such as colistin [58][59][60][61][62], are expected in patients who developed such infection after allo-SCT. Our results showed the higher risk of fatal infectious complications in post-transplant patients with ATL.…”
Section: Discussionmentioning
confidence: 99%